2006
DOI: 10.1021/bm061010g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Peptide-Based Polymers by Microwave-Assisted Cycloaddition Backbone Polymerization

Abstract: The optimized reaction conditions for the Cu(I)-catalyzed N-->C polymerization of azido-phenylalanyl-alanyl-propargyl amide to yield either high molecular weight linear polymers or medium-sized cyclic polymers is described. These reaction conditions will be applied to tailor the synthesis, properties, and structure of biologically relevant peptide-based biopolymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 34 publications
1
41
0
1
Order By: Relevance
“…Microwave irradiation was used to ensure a complete modification of the alkyne endgroups [31]. Via this approach, divalent (33, 37 -40, 43, 45, 46, 48), tetravalent (34,41,44,47,49), octavalent (35,42), and hexadecavalent (36) dendrimeric peptides were synthesized. Not only small (di)peptide-based azides but also unprotected biologically relevant larger (e.g., Leu-enkephalin 29, part of the anti-microbial peptide magainin 30, a fibronectin active fragment 31), even cyclic, azido peptides, e.g., an a V b 3 integrin binding RGD-containing peptide 32 have been efficiently converted into the corresponding dendrimeric cycloaddition products, as shown in Figure 4.…”
Section: Multivalent Dendrimeric Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave irradiation was used to ensure a complete modification of the alkyne endgroups [31]. Via this approach, divalent (33, 37 -40, 43, 45, 46, 48), tetravalent (34,41,44,47,49), octavalent (35,42), and hexadecavalent (36) dendrimeric peptides were synthesized. Not only small (di)peptide-based azides but also unprotected biologically relevant larger (e.g., Leu-enkephalin 29, part of the anti-microbial peptide magainin 30, a fibronectin active fragment 31), even cyclic, azido peptides, e.g., an a V b 3 integrin binding RGD-containing peptide 32 have been efficiently converted into the corresponding dendrimeric cycloaddition products, as shown in Figure 4.…”
Section: Multivalent Dendrimeric Peptidesmentioning
confidence: 99%
“…In most of the cases, (partially) protected building blocks are required and after the synthesis of the polymer, the protecting groups have to be removed, which is not a trivial task. The possibility of the chemoselective azide -alkyne coupling in the presence of other unprotected functional groups and the topological similarities between peptide amides and 1,2,3-triazoles [34] made us decide to explore the Cu(I)-catalyzed 1,3-dipolar cycloaddition reaction for the synthesis of peptide-based polymers [35]. In our studies, we used model dipeptide azido-phenylalanyl-alanyl-propargyl amide 51 (Scheme 3) which could be efficiently converted into high molecular weight amino acid-based polymers (up to 45 kDa).…”
Section: Multivalent Dendrimeric Peptidesmentioning
confidence: 99%
“…Previous studies regarding the effect of monomer dilution during the CuAAC step-growth polymerization of a-azide-w-alkyne monomers have shown that yields of monocyclization as high as 60 % could be attained using monomer concentrations of about 1 mm. [14] To improve the yield and efficiency of macrocycle formation, cyclization experiments were performed using a peristaltic pump for the controlled addition of monomer solutions to a solution of the catalytic system maintained at 60 8C. In this way, the reaction mixture contains a relatively dilute solution of the monomer at all times, and the monomer is exposed to a much higher concentration of catalyst to ensure a fast CuAAC intramolecular reaction.…”
mentioning
confidence: 99%
“…The selectivity of this reaction proved to be a striking consequence of the mechanistic constraints posed by the 1,3-copper(I) catalyzed cycloaddition itself. Following the bibliography reports indicating that most of the peptide-based biopolymers derive their structural, mechanical, and biological properties from sequential repetitions on their backbone (e.g., collagens, elastin and spider silk, antifreeze proteins, mussel glue, and reflectins), [43] in a study aimed to mimic such natural peptide biopolymers with repetitive sequences, Liskamp and coworkers [44] developed a method to prepare high molecular weight linear or medium-sized cyclic polypeptides based on click chemistry ( Figure 1C). Their work relied on the polymerization of azido-phenylalanyl-alanyl-propargyl amides by a microwave-assisted 1,3-dipolar polycycloaddition reaction.…”
Section: Peptidesmentioning
confidence: 99%
“…It was for example proven that microwave heating was in general superior to conventional heating for direction of the reaction outcome in such high molecular weight polymers. Following the same approach, Angell and Burgess [46] achieved the synthesis of SH2 domain-binding peptides and their open-chain analogs by reacting with monomers containing a single azide or alkyne group each [46] while van (C) Liskamp and coworkers [44] approach to linear and cyclic polypeptides. Reaction using CuSO 4 /Na ascorbate or Cu(OAc) led predominantly to linear polymerization, while with lower monomer ratio and Cu(OAc), cyclic products were obtained.…”
Section: Peptidesmentioning
confidence: 99%